2020
DOI: 10.3389/fpsyt.2020.00804
|View full text |Cite
|
Sign up to set email alerts
|

The Unhappy Mental Health Triad: Comorbid Severe Mental Illnesses, Personality Disorders, and Substance Use Disorders in Prison Populations

Abstract: Background: Information on the comorbidity of mental health problems in prison populations is scarce. The aim of the present study was to assess the prevalence of comorbidities at intake to prison between three diagnostic groups: severe mental illnesses (SMIs), personality disorders (PDs), and substance use disorders (SUDs). The cooccurrence of those disorders in prison populations may require the integration of differential treatment approaches and novel treatment trials. Methods: A consecutive sample of N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 35 publications
1
17
0
4
Order By: Relevance
“…Many individuals experience recurrent psychiatric hospitalizations and incarcerations over time—the so called revolving door phenomenom [19] , [20] , [21] . Repeated episodes of inpatient treatment and imprisonment have been reported for people with severe mental illness, comorbid substance use and personality disorders [22] . In 1939, Penrose described for the first time a possible inverse relationship between the number of psychiatric beds and the size of prison populations, based on a cross-sectional analysis of data from 18 European countries [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals experience recurrent psychiatric hospitalizations and incarcerations over time—the so called revolving door phenomenom [19] , [20] , [21] . Repeated episodes of inpatient treatment and imprisonment have been reported for people with severe mental illness, comorbid substance use and personality disorders [22] . In 1939, Penrose described for the first time a possible inverse relationship between the number of psychiatric beds and the size of prison populations, based on a cross-sectional analysis of data from 18 European countries [23] .…”
Section: Introductionmentioning
confidence: 99%
“…The young people in this study reported that, from their experiences, the interventions they participated in focused primarily on drug problems, and other problems or needs were neglected. Co-morbidity is a rather common problem among drug consumers, in particular in prisons (Mundt & Baranyi, 2020). Some of our interviewees experienced a lack of help in relation to mental health problems.…”
Section: Low Motivation To Participate In Interventionsmentioning
confidence: 99%
“…1 Violent offenders constitute a heterogeneous group, with some demonstrating very complex psychiatric comorbidities (e.g., forensic psychiatric patients) and others predominantly criminogenic needs. However, common denominators for violent offenders housed in forensic settings are difficulties with emotion regulation, impulsivity, and empathy in combination with different mental disorders (e.g., antisocial and other personality syndromes) (Bogaerts et al, 2012;Lobbestael et al, 2015;Filov, 2019;Mundt and Baranyi, 2020). Given this, maintaining an environment that reduces the risk of aggression represents a distinct challenge.…”
Section: Introductionmentioning
confidence: 99%